PENGARUH PEMBELAJARAN KOOPERATIF TEKNIK DUA TINGGAL DUA TAMU (TWO STAY TWO STRAY) TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 19 BANDAR LAMPUNG TAHUN PELAJARAN 2014/2015 - Zainal, Vetri Yanti (LPPM STKIP PGRI Bandar Lampung, 2016)
In the process of learning the use of media or learning models is very important because it can cause desire and interest in learning a new one that is expected to improve learning outcomes. In this regard the issues raised in this study is whether there is an influence of using cooperative learning techniques two stay two guests (two stay two stray) to the learning outcomes of integrated IPS second semester of eighth grade students of SMP Negeri 19 Bandar Lampung in academic year 2014/2015. The purpose of this study was to determine the effect of the use of cooperative learning techniques two stay two guests (two stay two stray) to learning outcomes of integrated IPS second semester of eighth grade students of SMP Negeri 19 Bandar Lampung in academic year 2014/2015. The method used in this research is the experimental method. The population in this research is all class VIII Semester even SMP Negeri 19 Bandar Lampung in the academic year 2014/2015 a total of 11 classes to 302. And the number of students who take the sample in two classes, one class as an experimental class and the other class as the control class. The sampling technique used in this study is a random cluster sampling technique. Data analysis was done by statistical quantitative data by using t-test formula that data relating to the figures obtained by the students after the test. Based on the hypothesis testing results obtained using thit thit = 7.66 and from 0.05 significance level distribution tables known ttab = t (1 - Â½a) = 2.02 and t (1-Î±) = 1.68. It can be concluded that the entire hypothesis proved to be true, which means that there is influence of using cooperative learning techniques two stay two guests (two stay two stray) on learning outcomes IPS Integrated second semester of eighth grade students of SMP Negeri 19 Bandar Lampung in academic year 2015/2016. The average results of social studies integrated students who use cooperative learning techniques two stay two guests (two stay two stray) higher than the results of social studies integrated students who do not use cooperative learning techniques two stay two guests (two stay two stray) against results Integrated social studies second semester of eighth grade students of SMPN 19 Bandar Lampung in academic year 2014/2015.